Keunikan Gereja Tubuh Kristus dalam Terminologi Misi dan Teologi Paulus - Harefa, Darmianus; Tengkue, Anggreini Angelina (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2023)
The purpose of this research is to see the uniqueness of the concept of the church and the concept of the mission of the body of Christ discussed in Paul's theology. This research uses descriptive qualitative research methods, with the aim of explaining the concept of the church as the body of Christ sourced from articles and books that discuss this concept. So that the result is that Paul discusses the concept of the body of Christ in more depth in Romans, 1 Corinthians, Colossians and Ephesians. This term is based on the concept of "many in one" which is the basis of Paul's theological doctrine of salvation. The basic concept of the body of Christ is that as the people of the New Testament God, the church itself is in Christ. The concept of the Body of Christ was only revealed to the Apostle Paul, and was marked starting from his conversion and juridically at his sending in Acts 13. Christ is the Christological center of the "people of God", namely the headship of Christ and all believers are its members. Typically, the mission in the Body of Christ Church is that Christ died, was buried and was resurrected and this good news is preached to everyone without discrimination, race, ethnicity or social status.